FREEZING CAPABILITY OF PASUNDAN BULL SPERM USING TRIS-EGG YOLK, TRIS-SOY, AND ANDROMED DILUENTS - Baharum, Abdullah; Arifiantini, R. Iis; Yusuf, Tuty Laswardi (Jurnal Kedokteran Hewan, 2017)
The aims of this study were to investigate the freezing capability of Pasundan bull spermatozoa in Tris-egg yolk (TEY), Tris-soy (TS), and AndroMed as diluents. Semen were collected twice a week from four Pasundan bulls aged 3-5 years old using an artificial vagina and evaluated macro- and microscopically. Semen had 70% sperm motility, 800x106/mL sperm concentration, and less than 20% sperm abnormalities were divided into three parts and each of them diluted with TEY, TS, or AndroMed. After an equilibration step at 5C for four hours, diluted semen were packaged in 0.25 mL straw, frozen in liquid nitrogen for ten minutes and kept in liquid nitrogen container until examination. Motility test on fresh, diluted, equilibrated, and after-thawed semen was done using Androvision. The results showed that after thawing motility of sperm diluted in AndroMed (58.640.72%) was higher than in TEY (49.451.22%) and TS (39.346.33%). Sperm motility of Pasundan bulls diluted in these three diluents reduced around 33.272.45% during freezing process.